Facile method for the synthesis of Co-core Au-shell nanohybrid - Sardar, Debasmita; Neogi, S. K.; Bandyopadhyay, Sanjoy; Satpati, Biswarup; Jain, Ruchi; Gopinath, Chinnakonda S.; Bala, Tanushree (New Journal Of Chemistry, 2014)
Heterostructured Co-Au core-shell nanoparticles have been synthesized by reducing AuCl4- ions on cobalt nanoparticles after a minor but effective modification of cobalt surface by an amine. The core shell morphology is emphatically confirmed by thorough investigation through UV-Vis spectroscopy, X-ray photoelectron spectroscopy (XPS), and transmission electron microscopic analysis (TEM). The chemical composition and topography were determined using STEM-HAADF analysis and EFTEM imaging. Fourier transform infrared (FTIR) spectroscopy confirms the surface modification of Co nanoparticles and the interactions involved between the ligands and the core and shell metals at various steps of the synthetic process. The magnetic properties confirm the material to be superparamagnetic in nature.

Facile synthesis of ZnO-Ag nanocomposite and its photocatalytic activity - Sardar, Debasmita; Maity, Jayeta; Ghosalya, Manoj Kumar; Gopinath, Chinnakonda S.; Bala, Tanushree (Materials Research Express, 2017)
The evolution of photoactive hybrid materials (e.g. noble metal-semiconductor) has resulted in heterogeneous photocatalysis. We report a facile route for the synthesis of ZnO-Ag nanocomposites with varying percentage of loading of the noble metal, expecting a great boost in the photocatalytic behavior of ZnO. The as prepared material was thoroughly characterized by UV-Vis, FTIR, TEM, FESEM, XRD, XPS analyses. The photocatalytic activities of the nanocomposites have been assessed from the ability to degrade methylene blue dye in aqueous solution. The results suggest that incorporation of Ag nanoparticles on the surface of ZnO particles can enhance catalytic activity in comparison to pure ZnO particles under visible light by minimizing the recombination of photogenerated electron-hole pairs.